Desarrollo de un software para el cálculo del nivel dinámico de fluido de un pozo mediante los datos de torque de varilla en un sistema de levantamiento artificial por bombeo de cavidades progresivas PCP (2018)
Currently, the "Echometer Well Analyzer" is the most used method to calculate the dynamic level of fluid in a well with artificial lift system by progressive cavities pumping, with some limitations and especially, with a high cost for the company that requires the service. This project proposes an alternative for the calculation of this level, a software that through calculations and equations allows obtaining the data without needing an additional investment, this is detailed explained considering parameters such as its design, development and functioning for a better understanding. The software was made with the QML language, based on Java Script. For the validation, the tests were carried out with said software and compared with the data thrown by the Echometer, thus achieving a marked similarity and a small error rate. The data validation will be carried out through a comparison between the data provided by the Echometer Well Analyzer for the company TDA Supply & Service S.A. In charge of providing the service to Well DT-081 located in Dina Terciario Field in the department of Huila; and the NAVI Software created and developed by the student exhibitors of the project. Finally, not only the usefulness and innovation of the software will be observed, which will save expenses for the company that needs to use it, but also the versatility and comfort of its use.